Fabrication of fish gelatin microfibrous mats by solution blow spinning - Vilches, José Luiz [UNESP]; De Souza Filho, Men De Sá Moreira; De Freitas Rosa, Morsyleide; Sanches, Alex Otávio [UNESP]; Malmonge, José Antonio [UNESP] (FapUNIFESP (SciELO), 2019)
In this work microfiber mats of Nile tilapia (Oreochromis niloticus) gelatin were successfully fabricated by using Solution Blow Spinning technique. The concentration and viscosity of fish gelatin solution, in acid acetic/water (80% v/v), were correleted to the morphology and diameter of the gelatin microfibers. It was found that increased solution viscosity leads to increase of fibers diameters from approximately 280 nm at viscosity ~ 0.085 Pa.s. to approximately 1195 nm at viscosity ~ 1.877 Pa.s. The TG thermograms showed similar thermal profiles for all fibrous mat gelatins with thermal stability at temperatures below 180°C. The DSC curve showed two endothermic peaks being the second one, in the range of 100-130°C, strongly influenced by the microfiber diameters. It shifts to higher temperature increasing the microfiber diameter. This behavior was associated to the diffusion of water in the microfibers. Combined DSC/TG results showed a significant influence of the microfiber diameter on the water absorption and desorption process.
Keywords: Fish gelatin; Gelatin microfiber; Nile tilapia; Solution blow spinning